Analysis of Public Perception of the Size (Placement) and Color of Dentures in Health Promotion Efforts - M. Bahrul Ilmi; Netty Netty; Deni Suryanto; Eddy Rahman (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
ntroduction: Dentures have many functions, of course, all of which are to improve health, but there are many factors that cause people to tend not to know the function of dentures. In Banjar Regency, there has not been a maximum in the equal distribution of dentists and dental nurses, which has the largest working area in Banjar Regency, so that people are more directed to dentists who specialize in dentures. The purpose of this study is to find out the public's perception of the function of dentures. Methods: This study is a quantitative analytical research with a cross-sectional approach using structured questionnaire instruments. The determination of the number of samples here is the community in the work area of the Aranio Health Center, Banjar Regency, using the Non-Probability Sampling technique, namely Quota Sampling, totaling 100 respondents. The instruments used in this study were in the form of questionnaires/interviews containing a list of statements about respondents' perceptions of denture function, perception of size (placement), and color of dentures. The data is processed and analyzed with Fisher Exact Test tests to test the research hypothesis. Results: The results of the study show that the level of public knowledge about the function of dentures is still relatively low, with the dominant respondents (96%) in the category of not knowing, where this condition shows a gap between public perception and a more comprehensive understanding of the benefits of dentures. In terms of the size (placement) of dentures, the largest proportion of respondents were in the poor category (45%). In the aspect of denture color, the distribution of respondents was relatively balanced between the interested (45%) and uninterested (55%) categories. The results of bivariate analysis came from the variable size (placement) of dentures (p-value 0.625; OR = 1.743) and color of dentures variables (p value 1.000; OR=1.233) with the function variable of dentures, where the two variables have no meaningful relationship. Considering the limitations of statistical power, the imbalance of the data distribution and the gap of the confidence interval make the accuracy of the estimates limited. These findings indicate that low public understanding is more likely to be related to limited access to dental health information and education than to the characteristics of dentures used. Conclusion: The need to increase access to information and education on dental health so that suggestions for the provision of information about dentures as a learning medium, both from print and electronic media dedicated to the immediate families of denture users, to reduce the reluctance to seek information. Health workers maximize their knowledge about the function of dentures in carrying out health promotion.